Strategi Komunikasi Branding Pariwisata Halal Berbasis Smart Tourism di Tana Toraja - Artianasari, Nining; Nurhakki; Musmuliadi (KOMUNIDA : Media Komunikasi dan Dakwah, 2024)
The natural charms of Tana Toraja and North Toraja districts have grown into world tourism magnets. Tana Toraja attracts many tourists because of its peculiarities and attractive destinations, such as cultural natural and sports tours" menjadi "such as cultural, natural, and sports tours. This research aims to study effective communication methods to promote the concept of halal in Tana Toraja tourism, which is one of the non-Muslim minority areas. This study uses the Qualitative Case Study Approach and Purposive Sampling Techniques. This study shows that government communication is crucial to improving understanding of the value and benefits of halal tourism. Halal tourism emerged because of two things: the religion of the owner and the cost. In Tana Toraja, halal tourism development is different because Muslim tourists' interest is very high. As a result, the entrepreneur is responsible for this initiative, and the basic halal standard is considered very important. Therefore, it is important to implement the "branding" of halal tourism. The government needs an effective tourism communication strategy model to build halal tourism.